Non-Standard Spelling in Wattpad Comments - Ayumi, Ayumi (Vivid: Journal of Language and Literature, 2023)
Non-standard spelling on social media refers to the use of unconventional spelling and grammar. This article explores the non-standars spelling used by Wattpad readers in their comments. The study employs descriptive approach. The data are comments posted by Wattpad reader in reaction to a story by Shin_an Yuki's story Haf Soul Part 17: Takdir Yang Aneh. The finding shows that Wattad readers employ spoken-like spelling, repetition of letters and punctuations, shortening, and letters deletion in their comments.